ANALISIS SPASIAL INDEKS KEKERINGAN DAERAH PANTAI UTARA (PANTURA) JAWA BARAT - Nasution, Ch; Syaifullah, Djazim (Center for Environmental Technology, 2005)
Spatial analysis for water deficit in Pantura was done for 16 rainfall stations average 13 year observations. Water balance computation was calculated with Thornthwaite-Matter method. Spatial analisys was done by Geographys Information System (GIS) with ArcInfo 3.5 and displayed by ArcView 3.3. Water balance analysis shown that water deficit was on June for most of all stations and reached maximum deficit on August. Water deficit was concentred around of Batujaya (bekasi District), Peundeuy (Karawang district), and around of Leuweungsemut (Indramayu district). These result of the analysis recommended to plan the optimum water management for maximize purpose of Jatiluhur Lake Ã‚Â Kata kunci : Analisis spasial, Thornthwaite-Matter neraca air, indeks kekeringan